Penguasaan Kaedah Nahwu sebagai Upaya Meningkatkan Kemampuan Membaca Bahasa Arab - Afifuddin, Muhammad (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2022)
The ability to read Arabic texts is largely determined by the mastery of the Nahwu rule and carefulness in determining the position of the sentence and the address of i'rab. This study aims to prove the theory that the ability to read Arabic texts has an important role in influencing Arabic skills, namely the correlational mastery of nahwu rules with the ability to read Arabic texts of STIT Al-Fattah students in semester VI. This study uses a quantitative research method with a research sample of 19 students VI. The results show that one of the Arabic text reading skills has a significant correlation with Arabic language skills. Because with good grammar mastery in Nahwu rules, it will make it easier for someone to master Arabic skills, one of which is the ability to read Arabic texts.